Greta Garbo and the Stock Cube: Film-themed Sweepstakes with Commercial Purposes in the Years of Fascism - Mariapia Comand (Cinergie)
The essay explores the phenomenon of film-themed contests, particularly those promoting consumer goods, in Fascist Italy. From this starting point, it examines the relationships between the media industry, the broader industrial sector, the bureaucratic apparatus, political power, and legislative authority, when the international dominance of Hollywood overshadowed the Italian market. The article considers ephemera as a complex discursive system in which the relationships and tensions between different and sometimes competing subjects and interests can be revealed. In particular, the study begins by reconstructing the phenomenon of prize competitions and sticker albums to promote products and brands. It outlines the forms of collaboration between cinema, businesses and commerce, and the role of ephemera within these dynamics. It then examines the fluctuating legislative interventions on contests and picture cards, symptomatic of a contradictory and opaque governmental stance. The article also explores the issue of the right to one’s own image, identifying a link between the emergence of image rights and the ephemeral dimension. Furthermore, it looks at the conquest strategy of the major Metro Goldwyn Mayer, characterised by the extensive use of ephemera. On the methodological level, the essay tests the “anatomy of ephemera”, which starts from the analysis of a specific ephemeron: the trading sticker album “Concorso del Leone. 100 artisti della Metro Goldwyn Mayer” (1937). The methodology is based on the conviction that a specific historical object is imbued with traces of past processes and can guide research toward new directions.